2017
DOI: 10.1002/acr.22980
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors for the Presence and Development of Vertebral Fractures in Patients With Ankylosing Spondylitis

Abstract: In this large AS cohort in daily clinical practice, radiographic vertebral fractures were frequently present in AS, especially in older patients with more advanced disease, low hip BMD, and a less healthy lifestyle. Interestingly, NSAID use was associated with a reduced vertebral fractures risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 43 publications
3
34
1
1
Order By: Relevance
“…In our study, prevalent and incident VFs were observed in patients receiving NSAIDs and TNF blockers, even if it is impossible to definitively conclude because of the low number of incidental events. Unlike other studies,23 24 we did not identify any risk factors of VF related to SpA disease but the small number of events, making impossible any definitive interpretation. These discrepancies can also be explained by the different methods used for vertebral fracture diagnosis (semiautomated, semiquantitative, qualitative, etc).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In our study, prevalent and incident VFs were observed in patients receiving NSAIDs and TNF blockers, even if it is impossible to definitively conclude because of the low number of incidental events. Unlike other studies,23 24 we did not identify any risk factors of VF related to SpA disease but the small number of events, making impossible any definitive interpretation. These discrepancies can also be explained by the different methods used for vertebral fracture diagnosis (semiautomated, semiquantitative, qualitative, etc).…”
Section: Discussioncontrasting
confidence: 83%
“…Both the prevalence and the incidence of VFs reported in our study are lower than that reported in previous studies. Prevalence of VFs ranges from 4% to 42% 22–28. Data from large databases assessed the relationship between SpA and clinical VFs 29 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2-year follow-up randomized controlled study showed that continuous non-steroidal anti-in ammatory drug treatment could reduce the progression of spine imaging in patients with AS [22]. Previous studies also reported that continuous NSAID treatment could reduce the risk of fracture in patients with AS [23].…”
Section: Discussionmentioning
confidence: 99%